KEBIJAKAN PEMERINTAH KOTA MEDAN DALAM PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA DIPASAR SIMPANG LIMUN KOTA MEDAN - Nasution, Zainuddin (Fakultas Agama Islam, 2019)
Development of Medan City, number, growth, employment, sector, formality, formal sector, sectoral, sectoral, sectoral, street vendors as one of the informal sectors that are often carried out with the informal sectors, with negative impacts, the environment, slums and disorderly. But there is a need for street vendors by the community to make street vendors even more. Medan City Government through Regional Regulation No. 31 of 1993 Jo the Mayor of Medan Letter No. 54 / SK / 1994 and Mayor Regulation No.8 of 2009 concerning the prohibition of trading on patterned roads, sidewalks, and road shoulders are still ineffective. Which is marked by the number of rounds carried out by street vendors. This research aims to study the characteristics, structuring and empowerment process, the benefits of structuring and empowering, as well as understanding of the development in structuring and empowering street vendors. The existence of street vendors involving the City Limun Intersection is considered as a cause of traffic jams and differences in the beauty of the city. In connection with the New Market Thoroughly The Medan City Government reviewed the arrangement and empowerment of street vendors who were originally selling along the shoulder roads in the Simpang Limun Market in Medan City by relocating them in existing markets. Medan City Regional Market Company. The purpose of this study is to describe and analyze the policies on structuring and empowering street vendors, applying the policies on structuring and empowering street vendors, as well as efforts to protect the policies on structuring and empowering street vendors in Medan's Simpang Limun Market. This research uses descriptive type using qualitative methods. Data collection techniques used include the method of observation, interviews, and documentation. Street vendors at Medan's Simpang Limun Market have not been going well. This is due to the fact that many street vendors who have joined the New Market have not been well served due to the disposition of market managers and policy implementers. This caused many traders to choose not to sell anymore in the New Market Thoroughly and chose to sell again along the SM road. Raja Pasar Simpang Limun Medan City.